The Effect of Employee Welfare Level and Work-Life Balance on Employee Performance: A Case Study of Gaming Centers in Malang City - Titus Dwi Meilina; M. Bukhori (Universitas KH. Abdul Chalim Mojokerto, 2026)
The entertainment industry, especially gaming centers in Malang City, faces challenges in maintaining employee performance due to low welfare and work-life imbalances. This study aims to examine the influence of employee welfare level and work-life balance on employee performance at gaming centers in Malang City. This study uses a quantitative approach, involving 50 employees selected through purposive sampling. Data were collected through an online questionnaire and analyzed using multiple linear regression. The results of the study show that partially, the level of employee welfare does not have a significant effect on employee performance, while work-life balance has a positive and significant effect. Simultaneously, these two variables have a significant effect on employee performance, with a contribution of 35.7% to performance variance. These findings show that work-life balance is the dominant factor in improving employee performance in the gaming center industry, exceeding the role of material welfare. Management is advised to prioritize flexible scheduling and employee well-being programs to maintain service quality.